Expansion of Knowledge, Practice and Public Policy with the ICD-11 for Psychologists and Mental Health Professionals: A Literature Review and Critical Analysis - Hualparuca-Olivera, Luis (2023)
Background: Mental disorders are alterations in several functional domains of human beings that trigger greater morbidity and mortality if not adequately addressed. The International Classification of Diseases 11th Edition (ICD11) is a recently approved modern global system to guide clinical practice for these disorders and other conditions. State of the art: Despite the imminent implementation of this system in member states, the guidelines on its scientific basis, practice and importance in public health have been published in a scattered manner, with a mainly psychiatric medical target audience, hence, it is necessary to unify these guidelines in a single text. Therefore, the objective of this review was to analyze three associated aspects: (a) current knowledge of the subject, (b) its application in psychological practice, and (c) reflection on the implications for public health policies. To do this, these aspects were divided into 10 sections with the most relevant topics, and examples have been described to facilitate their use and comments to promote their understanding. Conclusions: This paper presents a review that comprehensively addresses knowledgepractice- policy triad of mental disorders of the ICD-11. Authors’ contributions The authors participated equally in the preparation of this paper